Investigating the intention to work overseas among Filipino engineering students by testing a structural equation model based on an extended theory of planned behavior - Mediran, Marc Gabriel S.; Revilla, Josefa Angelie D.; Caroche, Maria Liezel P.; Mercado, Alan Marco S.; Villanueva, Marc Joseph S. (2021)
This study examined the antecedents of Filipino engineering students’ intention to work overseas, applying the theory of planned behavior (TPB) (involving attitude, subjective norm, and perceived behavioral control) extended with migration push and pull factors (PPF) (involving salary and compensation, career prospects, and quality of life). Structural equation modeling using 1,706 questionnaire responses proved that the PPF dimensions were indistinguishable, while another factor distinct from attitude, evoking the perceived enjoyment of working overseas (PEJ), emerged. The TPB and PPF were identified as important antecedents of intention (R2 = 0.667). PEJ had no direct effect on it but was significant along with PPF in explaining attitude, which mediated PEJ and PPF’s indirect effects on intention. Additionally, evidence was found for the moderation and effects of student characteristics (including gender, year level, school type, income group, and migration network). The findings provide opportunities for integrating human factors into labor migration-related strategies.
Keywords: Attitudes and opinions; Labor migration